Effect of pharmaceutical care intervention on blood pressure of elderly outpatients with hypertension (Revista Brasileira de Ciências Farmacêuticas, 2008)
The purpose of this study was to evaluate the effect of pharmacist intervention on the prevention and solution of drug therapy-problems (DTP), Body Mass Index (BMI), and blood pressure control in elderly outpatients with hypertension. The instruments were applied to 30 elderly outpatients assisted at the pharmacy of a primary health care unit in Ribeirão Preto (SP), Brazil. The group of patients received follow-up during a period of 12 months. It was observed that Pharmaceutical Care intervention optimized the medication use; reduced symptoms caused by drug therapy and improved the elderly patients' health conditions. The Pharmaceutical Care intervention influenced the care given to elderly people as well as the achievement of positive health outcomes. After this study, the researcher gave training about practice of Pharmaceutical Care to 38 dispensing pharmacists from the Public Health-System of Ribeirão Preto. Nowadays, these pharmacists are perpetuating the practice introduced in the region.